Real space electron delocalization, resonance, and aromaticity in chemistry - Leonard Reuter (Nature Portfolio, 2021)
The concept of delocalization, resonance and aromaticity are commonly discussed within electronic structure frameworks relying on specific wave function expansions. Here the authors propose a redefinition of these concepts from first-principles by investigating saddle points of the all-electron probability density.